La fabrique des délivrances et des réductions - Maïté Recasens (Les Cahiers de Framespa)
As part of this collective reflection on the production of sources of memory at the time of the end of the war, this article proposes to compare the corpus of urban memories produced by the consuls and the monarchs during the Wars of Religion (1562-1598). Two conceptions of the political use of memory seem to oppose each other: at the end of urban confrontations, certain Catholic consuls exalt the memory of their victory to remind people of their domination, while the monarchs seek to stifle the noise of fratricidal conflicts to allow a pacifying end to the wars. The goal is to understand how the authorities of the government and the monarchy sometimes impose silence, sometimes memory, according to their political interests at the time of the end of the war.